What will students learn about disability from pictures in school books? - Greniuk, Angelika (Disability and education, 2023)
The visual dominates over the text – modern man homo videns prefers the image, which is quicker and easier for him to assimilate, it also has more significance than the word. The image, like the text, carries its own message, creating a way of knowing and perceiving a given reality (Szpunar, 2008; Sztompka, 2005).School textbooks contain many visual elements, providing a separate and additional source of information. Disability and people with disabilities are presented visually very rarely. Nevertheless, it is possible to establish the ways and messages of depicting disability in school textbooks and to determine what students, including students with disabilities, can learn about disability from images in school textbooks. This article presents the results of a study of this issue. It is part of the results from a larger research project entitled. ’The (non-)presence list. Disability in school textbooks’, by Dr Marta Sałkowska, Magdalena Kocejko, Magda Szarota and Angelika Greniuk, implemented by Collegium Civitas in 2021.